Investigating the relationship and effect between health anxiety level and severity of cyberchondria in surgical patients (Bangladesh Journal of Medical Science, 2026)
Background The uncertainty of the results of surgical interventions and the patient’s fear of undergoing surgery increase health anxiety. The increased level of anxiety leads the individual to search for online information that is easy to access and cost-effective. Aim This study aimed to investigate the relationship and effect between anxiety level and severity of cyberchondria in surgical patients. Methods The study was descriptive, correlational, and exploratory. Data were collected using the Personal Characteristics Form, Health Anxiety Inventory, and Cyberchondria Severity Scale Short Form (CSS-12). The study was conducted with 300 surgical patients in the postoperative period between July and November 2023. Correlation and multiple regression analyses were performed to investigate the relationship between health anxiety and cyberchondria severity. Results There was a moderate positive correlation between participants’ health anxiety and cyberchondria severity scales (r=0.422 p